Perubahan Kombinasi Bisnis Implementasi Dan Dampak PSAK 22 Terhadap Kinerja Keuangan Perusahaan - Silmi Humaira Harahap; Suci Ralita Lestari; Naufal Fauzan Hsb; Bana Ahmad Gautama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Using a literature research methodology, this paper investigates how business combination accounting was implemented both before and after PSAK 22, which is now known as PSAK 103 on Business Combinations. This research analyzes profit margin, return on equity (ROE), and return on assets (ROA) to assess the impact of PSAK 22 on the business's financial performance. Prior to PSAK 22, businesses often employed the